Understanding maternal dietary choices during pregnancy: The role of social norms and mindful eating. (1st May 2017) - Hutchinson, A.D.; Charters, M.; Prichard, I.; Fletcher, C.; Wilson, C.
Abstract: Introduction: Serious health complications associated with excessive weight have been documented for pregnant women and their babies during pregnancy, birth and beyond. Whilst research has focused on identifying particular foods that can be either detrimental or essential for the developing baby, pregnant women's food choices are likely determined by broader considerations. This study examined social influences as represented in reports of descriptive and injunctive social norms related to healthy eating during pregnancy, and individual differences in mindfulness while eating, as important potential correlates of pregnant women's self-reported diet. Methods: Pregnant women ( N  = 139) completed a questionnaire that measured self-reported consumption of healthy and unhealthy foods, descriptive and injunctive norms related to healthy eating during pregnancy and the Mindful Eating Questionnaire (MEQ). Hierarchical multiple regressions were conducted to assess the extent to which norms and mindful eating accounted for variance in consumption of both foods. Results: No significant associations were observed between perceived social norms related to diet during pregnancy and self-reported dietary behaviour. Mindful eating was found to play a role in pregnant women's eating behaviour, with the awareness subscale of the MEQ significantly associated with healthy eating and the emotional subscale associated with unhealthy eating. Age was also associated with consumption of unhealthy foods; younger pregnant women reported consuming more unhealthy snacks and fast food meals. Conclusions: The associations between mindful eating and dietary behaviour suggests that improving mindfulness related to food consumption before and during pregnancy may provide a strategy to address excessive gestational weight gain.